Optimized phase-coding method for absolute phase retrieval based on K-means algorithm - Cai, Bolin; Shen, Yuan; Wu, Jun; Yang, Yu; Wang, Yuwei; Wang, Mengyu; Chen, Xiangcheng; Zhang, Lei; Wang, Keyi (Journal of modern optics, 2021)
The phase-coding method for absolute phase measurement possesses a strong robustness because its codewords are encoded into phase domain rather than intensity. However, a misalignment problem arises between fringe order and wrapped phase in this method owing to random noises and image blurring, especially in the high-frequency fringes situation. Therefore, the measurement result is unavailable. To overcome this problem, an optimized phase-coding algorithm is proposed in the study. We use the sinusoidal patterns to generate two opposite binary masks, which can locate half of each codeword. Then, the K-means algorithm is used to correct the codewords errors. The accurate fringe order is obtained by merging two halves of codewords and the absolute phase is recovered afterward. The used method is experimentally verified by an established measurement system, and the results show the proposed method is robustness and efficiency.